Importance of disguising groundstrokes in a match between two top tennis players (Federer and Djokovic). Issue 1 (February 2023) - Dimic, Milos; Furuya, Ryosuke; Kanosue, Kazuyuki
At the elite level in tennis, players tend to "disguise" their stroke intentions, confuse the receiver's judgment, and interfere with their anticipatory response. How frequent and effective disguised strokes are used remains unclear. We tried to answer these questions by analysing performance differences in the two consecutive sets of the match in the 2019 Wimbledon final, played by two tennis greats. Our hypothesis was that by effectively disguising their stroke intention, the hitters in this match could establish tactical superiority. By utilizing frame by frame video analysis, we determined whether each groundstroke was done with disguised intention or not. A disguised stroke was defined as the stroke, whose Initial Stroke Intention (ISI) of the ball direction in the pre-contact phase differed from the actual post-contact trajectory. To judge the ISI, we analysed the hitters' cues during the pre-contact period, court movement before the loading phase (contextual observation), and body posture during the set-up phase (preparing the body for force generation). To investigate the effectiveness of disguised strokes, we evaluated the receiver's anticipatory movement as well as subsequent point dynamics. Our results show that both players, as hitters, created advantageous point dynamics (APD) (winners or advantage) while as receivers made incorrect anticipatory responses significantly more frequently to the disguised strokes than that of the undisguised strokes. As hypothesized, disguised strokes in the match between two tennis experts can be not only highly unpredictable but also efficient in creating a tactical advantage for the hitter and a disadvantage for the receiver.